Firms Bunching Response to Indonesian Income Tax Threshold - Nurfauzi, Ekananda Anggih; Nuryakin, Chaikal; Putra, Bramastia Candra (Universitas Negeri Semarang, 2019)
Presumptive tax policy is implemented internationally in common in order to ease the SME’s tax administration. Firms have an opportunity to respond or not to a certain tax policy in order to get lower tax burdens. There is a presumptive tax policy implemented in Indonesia which affects firms’ behavior in gaining and reporting their incomes. Firms tend to choose to have their incomes below the threshold that has lower tax burdens. As a developing country, Indonesia has certain firms’ charactheristics and systems that differs from developed country’ firms so there is a necessity to know that the responses of Indonesian firms regarding the implementation of presumptive tax policy. This study aims to analyze firms’ responses regarding presumptive tax implementation especially in Indonesia with a certain threshold of IDR 4.8 billion since 2013. This study uses the bunching estimation method dan firms’ tax return data from 2011 to 2016, that differs from other studies in which use survey data. Our study concludes that the presumptive tax implementation based on turnover value induces negative bunching phenomenon in Indonesia due to the lower tax burden for firms whose turnover value is above the threshold. This negative bunching indicated by the results of significant bunching estimation analysis in the period after the presumptive tax policy implemented. In contrast to the developed country’ firms, Indonesian firms tend to stay above the threshold, rather than below, to gain lower tax burden.